Brand safety: the effects of controversial video content on pre-roll advertising. Issue 12 (December 2018) - Bellman, Steven; Abdelmoety, Ziad H.S.; Murphy, Jamie; Arismendez, Shruthi; Varan, Duane
Abstract: Newspapers have reported instances of famous brands' ads running as pre-rolls to terrorist videos on YouTube. Subsequent brand safety fears have led to advertisers pulling their YouTube ads. This study, a lab experiment, tested the effects of program quality and content—particularly violent, sexual or extremist content—on pre-roll ads. The experiment used measures from studies showing significant broadcast TV content effects on mid-roll advertising, using more extreme cable TV content to increase the chances of finding significant effects on pre-roll ads. Overall, the effects were minimal, with no effects on brand attitudes, ad liking, or three ad memory components—encoding, storage, and retrieval. In contrast to research showing program context effects on mid-roll advertising, context effects (e.g., on brand safety) do not seem an issue for pre-roll ads. A brand's reputation might suffer negative effects from pre-roll advertising in other ways, however. A limitation is that this study did not re-test the effects of controversial content on mid-roll advertising.